Pengembangan Media Web Figma untuk Meningkatkan Pemahaman Siswa Mengenai Materi Pemrograman Absolut CNC Milling - Mohamad Rendy Irfansyah; Ari Dwi Nur Indriawan Musyono (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to develop and evaluate the feasibility and effectiveness of a web-based learning media using Figma on the topic of absolute manual programming in CNC Milling. This research employed a Research and Development (R&D) method with the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The subjects of this study were 71 students of grade XI Mechanical Engineering at SMK Negeri 1 Semarang, while the preliminary study was conducted with grade XII students who had completed the relevant study period, and the product implementation was carried out with grade XI students as the primary subjects. Data were collected through expert validation sheets, questionnaires, and pretest-posttest instruments. The results showed that the developed media achieved a high level of validity, with scores ranging from 82.5% to 95%, categorized as